Tax Insight For Tax Year 2012 - Murdock, M. Casey. (Apress : Imprint: Apress, 2013)
Tax Insight: For Tax Year 2012 will teach you to take control of lifeỚ"s biggest expenseỚ taxes. In your lifetime, you will spend more money on taxes than on anything else. Despite that fact, you likely know the current prices of movies and milk but donỚ"t know what your marginal tax rate is. You know where to get the cheapest gallon of gas to save a buck or two, but you donỚ"t give a thought to the tax strategies you should be using right now that would save you thousands. Why? Is it too complicated and confusing? Too unpleasant? In Tax Insight, tax expert Casey Murdock opens up the world of taxes with amazing clarity and simplicity. As you will discover, you have within reach℗ numerous ways to reduce your taxes. With everyday language and real-life examples, Tax Insight will give you the keys℗ to minimizing your tax burden.℗ ℗ This book contains information you need even if you have a tax advisor or use a program like TurboTax. Tax professionals are busy and sometimes too cautious,℗ and ℗ programs often miss opportunities for you to save money.℗ It's also for those of all ages and income levels, including business owners. Tax Insight:℗ ℗ Breaks down the key components of taxes with ease and simplicity. Provides a roadmap to paying as little tax as possible. Helps you know if you should do it yourself or hire a professional. While there are many encyclopedic books on taxesỚ like J.K. LasserỚ"s Your TaxesỚ there arenỚ"t nearly enough that describe the tax code in plain language. Far more than a rehash of impenetrable IRS ỚShelpỚ<U+00fd> documents, Tax Insights is organized the way most people think and presents ideas in clear, simple language. If you buy this book and take advantage of its advice, you will save money.